EFFECT OF ALKALI TREATMENT AND MAPP ADDITION ON TENSILE STRENGTH OF SISAL/POLYPROPYLENE COMPOSITES - Sosiati, H.; Nahyudin, A.; Wijayanti, D.A.; Triyana, K.; ., Sudarisman (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Mechanical properties of composite are strongly influenced by surface treatment of fibers and fiber content. The study aimed to verify the influence of a modified fiber surface using an alkali solution and, the addition of maleic anhydride grafted polypropylene (MAPP) and both (alkali solution + MAPP) on increasing the tensile strength of sisal/polypropylene (PP) composites. The composites were fabricated using hot compression molding with a fiber content of 30 and 50 wt%. Untreated and alkali-treated sisal fibers with a fiber length of 2 mm were used. Various amounts (5, 10 and 15 wt%) of MAPP were added to the untreated sisal/PP and alkali-treated sisal/PP composites. The results indicated that the tensile strength of the untreated sisal/PP composite containing 50 wt% of fiber was higher than that of 30 wt% fiber content. The addition of 5 wt% MAPP into both untreated and alkali-treated sisal/PP composites significantly increased tensile strength compared to that of 10 and 15 wt% MAPP addition. Good interfacial bonding between sisal fiber and the PP matrix was observed at 5 wt% MAPP loading. Excessive MAPP content could form a barrier that tends to inhibit the stress transferred across the matrix-fiber interfaces.